A Modeling in the Theft Recidivists from the Perspective of Bandura - Nabila Athifa Wediana; Ira Darmawanti (Character Jurnal Penelitian Psikologi, 2023)
A high number of criminal theft phenomena in Indonesia are carried out by recidivists. Recidivism is the repetition of the same crime which causes the individual to return to being a prisoner within a certain period of time. Based on the preliminary study it was found that the perpetrator learned this theft from the closest person in his environment. This study aims to examine the process of the formation of repeated theft criminal behavior associated with modeling from the perspective of Bandura and the influencing factors. The research method used is a qualitative case study approach. Data was collected by means of semi-structured interviews with three participants and a thematic analysis was carried out. This study found that there is a pattern of learning theft behavior in recidivists, namely (1) attention process, the individual is interested in the theft after directly seeing the theft process being carried out (2)retention process, the strategy and criminal methods of theft are stored in the form of verbal and visual coding ( 3) motoric production, starting to try because of cooperation until they become used to it (4) motivational process, the behavior is maintained because stealing is considered a way to easily achieve needs. The ease with which criminal behavior is found in the surrounding environment and accepted becomes an external factor, while internal factors are low self-esteem, low self-control, and a long criminal history. The results of the analysis also show that this behavior is imitated and maintained by recidivists by considering rewards. Key word : Modelling, Theft recidivism, Bandura's perspective